Higher Circulating miR-199a-5p Indicates Poor Aerobic Exercise Capacity and Associates With Cardiovascular Dysfunction During Chronic Exposure to High Altitude - Huang, He; Xie, Shenwei; Gu, Xiaolan; Xiang, Bin; Zhong, Zhifeng; Huang, Pei; Gao, Yuqi; Li, Peng (Frontiers in Physiology, 2021)
Background: Hypoxia-induced decline in exercise capacity is ubiquitous among lowlanders immigrated to high altitudes, which severely reduces their work efficiency and the quality of life. Although studies have revealed that hypoxia-induced cardiovascular dysfunction limits exercise capacity at high altitude, the mechanisms have not been well explored at the molecular level. The miR-199a-5p is hypoxia-sensitive, and serves as an important regulator in cardiovascular pathophysiology. However, whether miR-199a-5p is involved in cardiovascular dysfunction at high altitude and contributes to subsequent reduction in exercise capacity remains unknown. Thus, this study aimed at exploring these relationships in high altitude population. Methods: 175 lowlanders who had immigrated to an altitude of 3,800 meters 2 years ago participated in the present study. The level of plasma miR-199a-5p and the concentration of serum myocardial enzymes were detected by qRT-PCR and ELISA, respectively. Indices of cardiovascular function were examined by echocardiography. The exercise capacity was evaluated by Cooper’s 12-minute run test and Harvard Step Test. Furthermore, we explored the biological functions of miR-199a-5p with silico analysis and biochemical test. Results: The level of miR-199a-5p was significantly higher in individuals with poor exercise capacity at 3,800 m, compared with those with good exercise capacity (p < 0.001). MiR-199a-5p accurately identified individuals with poor exercise capacity (AUC = 0.752, p < 0.001). The level of miR-199a-5p was positively correlated with cardiovascular dysfunction indices (all, p < 0.001). Furthermore, miR-199a-5p was involved in oxidative stress process. Conclusion: In this study, we reported for the first time that circulating miR-199a-5p level was positively associated with exercise capacity during chronic hypoxia at high altitude. Moreover, higher miR-199a-5p was involved in hypoxia-induced cardiovascular dysfunctions, thus contributing to poorer exercise endurance at high altitude.